2012
DOI: 10.1111/pim.12010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of serum cytokine levels in children with chronic cough associated with Toxocara canis infection

Abstract: Toxocara infection is associated with an increased prevalence of airway symptoms and may be a possible aetiologic agent of chronic cough. The occurrence of toxocariasis in Hungary is mild and/or sporadic. The purpose of this study was to investigate the levels of serum cytokines (IL-1, IL-2, IL-4, IL-5, IL-6, IL-10, IL-13, IFN-gamma and TNF-alpha) and total IgE, the blood eosinophil count, the results of skin prick and non-specific bronchus provocation tests in Toxocara-seropositive children with chronic cough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…18,19 An experimental study revealed that IL-6 limits the Th2 response, modifies the Treg-cell phenotype, and promotes host susceptibility to helminth infection. 19 Our observed elevated IL-6 levels in preschool-and school-aged children support the result of Nagy et al, 20 who reported elevated IL-6 level in children with Toxocara canis infection. Our observation might be a reflection of the function of IL-6 as an enhancer of the differentiation of Th2 cells, which are predominantly involved in the control of helminth infection.…”
Section: Discussionsupporting
confidence: 88%
“…18,19 An experimental study revealed that IL-6 limits the Th2 response, modifies the Treg-cell phenotype, and promotes host susceptibility to helminth infection. 19 Our observed elevated IL-6 levels in preschool-and school-aged children support the result of Nagy et al, 20 who reported elevated IL-6 level in children with Toxocara canis infection. Our observation might be a reflection of the function of IL-6 as an enhancer of the differentiation of Th2 cells, which are predominantly involved in the control of helminth infection.…”
Section: Discussionsupporting
confidence: 88%
“…Strong inflammatory lung reactions in human toxocariasis have been well described, which may trigger chronic hypersensitivity mediated by an eosinophilic environment and granulomatous inflammation. Eosinophilic granuloma enables pathogen neutralization; however, it may have deleterious effects on the host, and AAM may play an important role in decreasing inflammation and favoring tissue repair, although its role in toxocariasis is yet to be determined [33, 55, 56]. Similarly, studies on the role of ILC2s in tissue repair during toxocariasis are lacking.…”
Section: Role Of Macrophages During Tissue Migrating and Resident mentioning
confidence: 99%
“…Once in the small intestine of intermediate hosts (it can be paratenic hosts, such as humans or mice), larvae penetrate the gut wall and migrate to many organs, including the lung, liver, muscles, and central nervous system, resulting in significant pathology. Infection in the lung with T. canis L2 larvae can cause an asthma-type condition in children [3,4]; airway hyperresponsiveness, pulmonary inflammation, and increased levels of IgE can persist for months in mice experimentally-infected with T. canis [5,6]. Thus, assessing the inflammatory response, including defining roles for cells such as classically activated macrophages (M1) in the pathology following infection with T. canis is critical to a better understanding of the disease and the development of targeted therapies.…”
Section: Introductionmentioning
confidence: 99%